Gender inequalities in allocating time to paid and unpaid work: evidence from Bolivia - Marcelo Medeiros; Rafael Guerreiro Osório; Joana Costa (Levy Economics Institute of Bard College, 2007)
This working paper analyzes paid and unpaid work-time inequalities among Bolivian urban adults using time use data from a 2001 household survey. We identified a gender-based division of labor characterized not so much by who does what type of work but by how much work of each type they do. There is a trade-off between paid and unpaid work, but this trade-off is only partial: women's entry into the labor market tends to result in a double shift of paid and unpaid work. We also find very high levels of within-group inequality in the distributions of paid and unpaid work-time for men and women, a sign that, beyond the sexual division of labor, subgroup differentiation is also important. Using decompositions of the inequality in the distribution of total time spent at work, we show that gender plays an important role in determining the proportion of paid to unpaid work done by individuals, but it plays a lesser role in determining the higher total workload of some individuals relative to others.
Keywords: J16; J22; 330; Time Use; Domestic Labor; Unpaid Work; Double Shift; Sexual Division of Labor